Juventude, drogas e biopolítica - Vergara, Alcides Jose Sanches [UNESP]; Justo, José Sterza [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2011)
In this article, we tackle the issue of youth and drugs as something linked to biopower and biopolitics, both concepts developed by Michael Foucault. Youth and drugs are taken and analyzed in situations involving the management of crime linked to the risks and deviations from the law, abuse and dependence. The youth; irreverent, courageous, healthy, idealistic, and that wanted to change the world for the better as we have seen in the past, is now strongly related to violence, dangerous activities, moral and social risks, drug addiction, criminality, and others negative images. To deal with these young people, tolerance and small punishments of yore are not enough anymore. The young people emerge as a segment of the population subject to various actions and programs. The drugs now are seen as matters of security and public health. There is a shifting and repositioning in the discourse about the young - from minor, drugged, and criminal to lawbreaker, user and drug addict. The change is subtle, but represents a modulation in the devices of social control. Beyond the consent of the young to get rid of drugs, there is a search for the creation of a wide area of monitoring of their behavior through the activation of community protection networks. The belief that the young are more impressionable and vulnerable, and that action on the cause of the problem or risk reduction are the most efficient ways of management, taking responsibility away from personal and family sphere and transferring it to the State, contributes to the increasing control of young people nowadays.

En el presente artículo trataremos el tema de la juventud y de las drogas como una cuestión vinculada a la biopolítica y al biopoder, conceptos elaborados por Michael Foucault. La juventud y las drogas son analizadas en las situaciones que implican la gestión de la criminalidad. La juventud, irreverente, valiente, saludable, idealista y que quería cambiar el mundo mejorándolo, tal como fue retratada en otras épocas, hoy está siendo fuertemente asociada a la violencia, a peligros, riesgos personales y sociales, dependencia de drogas, criminalidad y otras imágenes negativas. Para lidiar con esos jóvenes no bastan la tolerancia ni los pequeños castigos de otrora. Los jóvenes emergen como un segmento de la población objeto de acciones y programas diversos. Las drogas pasan a ser vistas como asuntos de seguridad y de salud pública. Se observa un desplazamiento y reposicionamiento en el discurso acerca de los jóvenes: pasan de menores, drogadictos y criminales a infractores, usuarios y dependientes químicos. El cambio es sutil, pero representa una modulación en los dispositivos de control social. Se busca, además de la aceptación del propio joven en cuanto a librarse de las drogas, la creación de un amplio espacio de monitoreo de su conducta mediante la activación de redes comunitarias de protección. Para el control creciente de los jóvenes en la actualidad, también actúa la creencia de que éstos son más influenciables y vulnerables y que la acción en el origen del problema o la disminución de los riesgos es la forma más eficiente de gestión, retirando la responsabilidad de la esfera personal y familiar y transfiriéndola para la esfera del Estado.

No presente artigo, trataremos o tema da juventude e das drogas como uma questão vinculada à biopolítica e ao biopoder, conceitos elaborados por Michael Foucault. A juventude e as drogas são tomadas e analisadas nas situações que envolvem a gestão da criminalidade A juventude, irreverente, corajosa, saudável, idealista, e que queria mudar o mundo para melhor, tal como foi retratada em outras épocas, hoje, está sendo fortemente associada à violência, perigos, riscos pessoais e sociais, à dependência de drogas, à criminalidade e a outras imagens negativas. Para lidar com esses jovens já não bastam à tolerância e os pequenos castigos de outrora. Os jovens emergem como um segmento da população objeto de ações e programas diversos. As drogas passam a ser vistas como questões de segurança e de saúde pública. Observa-se um deslocamento e reposicionamento no discurso acerca dos jovens - de menor, drogado e criminoso para infrator, usuário e dependente químico. A mudança é sutil, mas representa uma modulação nos dispositivos de controle social. Busca-se, além da anuência do jovem para que se livre das drogas, a criação de um amplo espaço de monitoramento de sua conduta, mediante a ativação de redes comunitárias de proteção. Concorre para o crescente controle dos jovens na atualidade a crença de que são mais influenciáveis e vulneráveis e que a ação na origem do problema ou a diminuição dos riscos é a forma mais eficiente de gestão, retirando a responsabilidade da esfera pessoal e familiar e transferindo-a para a esfera do Estado.
Youth, drugs, and biopolitics
Juventud, drogas y biopolítica
Keywords: Modernity; Youth; Consumerism; Drugs; Criminality; Modernidad; Juventud; Consumismo; Drogas; Criminalidad; Modernidade; Juventude; Consumismo; Drogas; Criminalidade